Smart Classroom IoT-Based Android for Temperature and Humidity Monitoring to Enhance Student Learning Comfort - Dony Novaliendry; Yudhi Diputra; Irma Yulia Basri; Ihsanul Insan Aljundi; Frans Surya Pati Harau, (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study presents an innovative Smart Classroom IoT system based on the Android platform for monitoring temperature and humidity to enhance student learning comfort. The system integrates an Arduino microcontroller, DHT22 temperature-humidity sensors, and a dedicated Android mobile application for real-time environmental monitoring and control. The system automatically monitors ambient temperature and humidity conditions in classrooms and provides notifications to educational staff when environmental parameters exceed optimal ranges. Performance evaluation demonstrates significant improvements in environmental monitoring accuracy (±0.5°C precision), user satisfaction (4.6/5.0 rating), and energy efficiency through intelligent climate control recommendations. The Androidbased monitoring interface enables remote access to environmental data, historical trend analysis, and proactive environmental management. The system successfully maintained optimal learning conditions by providing continuous environmental monitoring and timely alerts for manual intervention when needed. This study contributes to creating comfortable learning environments while supporting energy-efficient facility management in educational institutions.